FENOMENA KEPERCAYAAN DAN AMALAN MASYARAKAT DALAM PERUBATAN ISLAM DI MALAYSIA - Ahmad Najaa' Mokhtar; Jahid Hj Sidek; Muhammad Khairi Mahyuddin; Abdul Rahim Zumrah; Mahyuddin Ismail; Rosidayu Sabran; Mohd Rumaizuddin Ghazali (Jurnal Ushuluddin Adab dan Dakwah, 2018)
The humanwill always expose with various diseases. In nature, they will find a suitable medicine for the particular disease. They can get the medicine either from the conventional medical center such as clinic or hospital, or through the alternative medical center such as the Islamic medical center or etc. In the Malaysian context, the Muslim community preferred to choose the Islamic medical approach to cure the disease, especially after they failed to recover from the treatment given by the conventional medical center. This study was conducted to describe the concept of Islamic medicine from the perspective of Islamic Akidah and Sharia. This study believes that the Islamic Akidah and Sharia should be the foundation for the Islamic medical approach, which has been ignored by the few Islamic Medical Center. This study also was conducted to identify the method and the implementation of Islamic medical at the Islamic Medical Center. To answer the previous objectives, a case study has been conducted. The case study was analyzed based on Al-Quran, hadis and the opinion of the Islamic scholars. The data for this study was collected from 24 Islamic Medical Center in Selangor. This study reveals that the of Islamic medical still needs for standard guideline to ensure the professionalism in this field.